Bioenergy with carbon capture and storage and shale gas: a comparative discourse analysis of two energy technologies in the context of the UK’s net zero transition - Trdlicova, Karolina (2025)
Contributing to the fields of energy and environmental policy studies, using Maarten Hajer’s (1995) framework of discourse analysis as its main analytical and methodological approach, this thesis focuses on two energy technologies, bioenergy with carbon capture and storage (BECCS) and hydraulic fracturing. This thesis expands on the existing knowledge and body of research in this area, by providing a comparative discourse analysis of the two energy technologies in the unique context of the UK’s net zero transition. Approaching energy technologies as inherently socio-technical systems, the choice of comparing shale gas and BECCS is justified in several ways. Both past and present energy policies described shale gas and BECCS as being able to contribute to decarbonisation to various degrees, being described as a lower carbon and a net zero carbon energy technology respectively. Although utilising different processes, one of storage and the other of extraction, the energy technologies share the use of underground space. Their low-carbon credentials are also points of contestation. Neither of the technologies is being deployed at a commercial scale in the UK, with shale gas having only been in exploratory stages and BECCS being trialled. Additionally, they share a tension between the substantial roles that the two energy technologies were envisioned to play in the UK’s energy mix at different points in time and the current lack of realisation of these roles. In 2019, the UK Government announced a legally binding target to bring all greenhouse gas emissions to net zero by 2050. Using purposive and snowball sampling, I have conducted 31 semi-structured interviews with key actors, between 2020 and 2021, during a time when the net zero transition was well underway. Working with the assumption that language is not a neutral transmitter and that the world is shaped by the language we use to describe it, this thesis used discourse analysis to answer how key actors make sense of BECCS and shale gas in the context of the net zero transition. More specifically, the thesis focused on how the participants’ understanding of shale gas and BECCS reflected in the language that they used to describe the energy technologies and the energy transition itself. I have analysed this using the discourse analytical concepts of ‘storyline’ and ‘discourse coalition’ and have then subsequently categorised the different visions of the net zero transition as presented in these discourse coalitions. By doing this I demonstrated that there is not a clear shared understanding of the role and potential of BECCS among key actors and that there is a wide range of views on the functionality, scalability, and sustainability of the technology. In contrast to previous findings, this research also showed that in the context of net zero transition, the shale gas discourse is less polarised. Instead of the expected two discourse coalitions, pro- and anti- shale gas, this discourse is divided into three, neither of which is distinctly pro-shale gas. Rather, the shale gas discourse coalitions differ in the way they make sense of the absence or failure of shale gas development in the UK. The thesis also demonstrated that it seems to be very difficult for key actors to make sense of and conceptualise future visions of both BECCS and shale gas without referencing the net zero transition and that there are three types of visions of the net zero transition among key actors. These visions vary widely in the way they understand the potential and role of the net zero transition, and most importantly in the way they view the relationship between shale gas, BECCS and the transition. These insights highlight the contentious nature of the energy debate and the discursive struggles within the net zero transition, which could ultimately shape the way in which the net zero transition develops and are therefore important to study and to pay attention to at this point.